Modalities to Treat Penile Glans Amputation: Case Series - Sukasah, Chaula L.; Atmodiwirjo, Parintosa; Anindhawati, Nur (Jurnal Plastik Rekonstruksi, 2012)
Background: In Indonesia, a country with Muslim population as a majority, circumcision is the most common operation performed in males. However, since circumcisions are also commonly performed by inexperienced individuals and during communal circumcision event, we frequently come across complications. One of the most severe complications is amputation of the penile glans. There are several techniques that can be used to treat this complication. In this paper we present some which have been used in our division and the result. Patient and Methods: We report three cases of traumatic penile glans amputation as a complication of circumcision that has been admitted to Cipto Mangunkusumo Hospital during January 2011 – January 2012. In first case we performed full thickness skin graft, in the second one we performed groin flap, and scrotal flap to reconstruct the third case. We evaluate the result for several months. Results: The three techniques showed no complication, good result in function and also aesthetically acceptable for patient and the family. Choice of technique that has been used to repair the amputated penis depended on the patient condition, and surgeon’s choice.Summary: The three techniques each has advantages and disadvantages, but all of them are acceptable, functionally and aesthetically.